(untitled) (Journal of Business Management and Accounting, 2019)
This study aims to examine the impact of regional expansion policy on regional development inequality in North Sumatra province, Indonesia. North Sumatra province is one of 34 Provinces in Indonesia. This province produce many new regencies and cities as a result of regional expansion policy. In 2000, the number of regencies in North Sumatra Province were 19 and then expanded to 33 in 2009. The number of regencies remain unchanged since then. The aim of regional expansion policy is to improve prosperity and accelerate development. Therefore, this study attempts to analyze whether the policy of regional expansion in North Sumatra Province achieved the purpose or rather caused development inequality in the regency. This study utilized the Williamson Index method to analyze the value of development inequalities in North Sumatra Province from 2000 to 2016 using data from all regencies in the province. The results show that the expansion of the regency has resulted in a high level of development inequality. This indicates that developmental inequality is increasing.